2 John Leeds Bozman, History of Maryland 116 (1837) (enacted 1639) - (:unkn) unknown (My University, 1639)
Gave the inhabitants of Maryland, who are Christians, all rights, liberties, immunities, privileges, and free customs as naturally born Englishmen.
Keywords: GUARANTEED RIGHT